Advances in research of ursolic acid and its derivatives as potential drug candidates against various types of lung cancers - Song, Li; Dai, Ling; Tan, Yan; Jiang, Kailin; Wei, Xueni; Hu, Yufei; Hu, Yalin; Lin, Jieying; Yao, Xu; Mi, Pengbing; Zheng, Xing (Medicinal chemistry research, 2023)
As one of the most common mortal diseases, the development of anti-lung cancer drugs is never stopped. Ursolic acid (UA) is a pentacyclic triterpenoid with significant anti-lung cancer activity and low toxicity. The bottleneck of UA in clinical application is poor water solubility and bioavailability. Until now, many novel UA derivatives have been developed to overtake these problems. In this paper, the relationship between the structure and activity of different functional groups was discussed. All anti-lung cancer ursolic acid derivatives were reviewed, and their biological activity and structure–activity relationship were described. The research progress of UA derivatives against various types of lung cancer was reviewed.